Human aldehyde oxidase (hAOX1): structure determination of the Moco-free form of the natural variant G1269R and biophysical studies of single nucleotide polymorphisms - Mota, Cristiano (2019)
This work was supported by the Applied Molecular Biosciences Unit-UCIBIO which is financed by national funds from FCT/MCTES (UID/Multi/04378/2019), Project PTDC/BBB-BEP/1185/2014 and Grant SFRH/BPD/ 84581/2012 (CC). SL thanks the Deutsche Forschungsge-meinschaft (DFG) for the support with Grant LE1171/8-3. The ESRF staff are also acknowledged, in particular ID30B beamline staff (ESRF, Grenoble).